Gaussian-Schell analysis of the transverse spatial properties of high-harmonic beams - Kevin O'Keeffe (Scientific Reports, 2016)
High harmonic generation (HHG) is a compact source of coherent, ultrafast soft x-ray radiation. HHG is increasingly being used as a source to image biological and physical systems. However, many imaging techniques such as coherent diffractive imaging, and ptychography require coherent illumination. Characterization the spatial coherence of HHG sources is vital if these sources are to kind widespread applications. Here a new method for characterizing coherent radiation is used to investigate the near- and far- field spatial properties of high harmonic radiation generated in a gas cell. The intensity distribution, wavefront curvature, and complex coherence factor are measured for a range of harmonic orders, and the Gaussian-Schell model is used to determine the properties of the harmonic beam in the plane of generation. Our results show the measured spatial properties of the harmonic beam are consistent with the finite spatial coherence of the driving laser beam as well as variations of the atomic dipole phase. These findings are used to suggest new approaches for controlling and optimizing the spatial properties of light for imaging applications.